2020
DOI: 10.1093/toxres/tfaa079
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage, inflammation, genotoxic effect, and global DNA methylation caused by inhalation of formaldehyde and the purpose of melatonin

Abstract: Formaldehyde (FA) exposure has been proven to increase the risk of asthma and cancer. This study aimed to evaluate for 28 days the FA inhalation effects on oxidative stress, inflammation process, genotoxicity, and global DNA methylation in mice as well as to investigate the potential protective effects of melatonin. For that, analyses were performed on lung, liver and kidney tissues, blood, and bone marrow. Bronchoalveolar lavage was used to measure inflammatory parameters. Lipid peroxidation (TBARS), protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…3A). To test this hypothesis, we first examined whether FA induces base damage, as oxidative lesions can be converted to 5’-flaps by the BER pathway 41 . Accordingly, we observed that FA elevated cellular levels of 8-oxo-deoxyguanine (8-OXO-dG) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). To test this hypothesis, we first examined whether FA induces base damage, as oxidative lesions can be converted to 5’-flaps by the BER pathway 41 . Accordingly, we observed that FA elevated cellular levels of 8-oxo-deoxyguanine (8-OXO-dG) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, melatonin also alleviated oxidative damage of lipids and DNA in primate liver [153] and peripheral blood lymphocytes of healthy, non-smoking males [154]. Additionally, in vitro and in vivo settings have illuminated the broad potential of melatonin to address the genotoxicity of stressors such as arecoline [155], lead ( [156]), formaldehyde [157], the endocrine-disrupting bisphenol A [158] or engineered titanium dioxide nanoparticles [159].…”
Section: Role Of Melatonin In Counteracting Sulfur and Nitrogen Musta...mentioning
confidence: 99%
“…FA is a potent mutagen that causes DNA strand breakage, DNA–protein crosslink breakage and oxidative damage to DNA bases. Bernardini et al (2020) used the comet test and MN assay to measure genetic damage in an in vitro experiment involving rat bone marrow mesenchymal stem cells. The comet test revealed a dose‐dependent increase in induced DNA strand breakage.…”
Section: Endogenous Fa In Pathological Statesmentioning
confidence: 99%